Impact on adult children caring for elderly parents with a long-standing mental illness - George, Kuruvilla; Fuller, Linda; Ancell, Jennifer (International Journal of Medicine, 2013)
Introduction: This research contrasts the experiences of long-term carers of elderly parents who have had a long-standing mental illness and first-time carers of parents who have become mentally unwell in old age. It was hypothesized that the children of elderly parents with a long-standing mental illness have differing needs when faced with the caring role compared to first-time carers of elderly mentally ill patients. Method: Using a qualitative research methodology and interpretive perspective, eight carers were interviewed using a standardized questionnaire from which salient issues were drawn and analyzed. Results: Long-term carers faced issues including a longer duration of care-giver stress, early entry into adult responsibilities of caring, frustrations concerning lack of recognition from mental health services and cumulative stress affecting long-term carers’ significant relationships and health. First-time carers sought earlier access to mental health services, specialist information about mental health issues and coping strategies for the care-giving role. Conclusion: It was found that both sets of carers (long-term and first-time), irrespective of the duration of their caring experiences, shared complex and competing demands on their physical and emotional resources. All carers were able to identify ways to improve support to improve support to children caring for ageing mentally ill parents.